Psychomedical Intervention Model for Servicemen Based on a Study of Mental Disorders - Shvets, A.V. (Кибернетика и вычислительная техника, 2019)
The purpose of the article — is to assem and to analyze the influence of various harmful factors in combat environment on the psychological status and mental health of military personnel and ex-combatants for development of psychomedical intervention model. Results. A retrospective summarizing of available information on the medical and psychological consequences of hybrid war relating to the characteristics of their aftereffects in recent years among military and demobilized persons has been performed. An assessment of stress factors impact at combat environment (physical, informational, organizational and anticipation) on military personnel participated in military conflict has been done. The specific features and structure of mental disorders in the military personnel, which were treated in hospital conditions have been revealed. The decision support model for reliable (p<0.001) prediction further adjustment disorders after extreme conditions has been developed. Мета статті — дослідити вплив різних шкідливих чинників в бойовому середовищі на психологічний статус і психічне здоров'я військовослужбовців і колишніх комбатантів для розробки моделі медико-психологічної допомоги. Результати. Проведено ретроспективне узагальнення наявної інформації про медичні і психологічні наслідки гібридної війни за останні роки, що стосується характеристик цих наслідків на військовослужбовців і демобілізованих осіб. Проведено оцінку впливу стресових факторів бойового середовища (фізична, інформаційна, організаційна та антиципаційна) на військовослужбовців, які брали участь у військовому конфлікті, які були згруповані в два основні чинники. Виявлено особливості та структуру психічних розладів у військовослужбовців, які проходили лікування в умовах стаціонару. Розроблена модель підтримки прийняття рішень для прогнозування подальших розладів адаптації після перебування в екстремальних умовах має високий ступінь достовірності (p < 0,001). Цель статьи — исследовать влияние различных вредных факторов в боевой среде на психологический статус и психическое здоровье военнослужащих и бывших комбатантов для разработки модели медико-психологической помощи. Результаты. Проведено ретроспективное обобщение имеющейся информации о медицинских и психологических последствиях гибридной войны за последние годы, касающееся характеристик этих последствий на военнослужащих и демобилизованных лиц. Проведена оценка воздействия стрессовых факторов боевой среды (физическая, информационная, организационная и антиципационная) на военнослужащих, участвовавших в военном конфликте. Выявлены особенности и структура психических расстройств у военнослужащих, проходивших лечение в условиях стационара. Разработанная модель поддержки принятия решений для прогнозирования дальнейших расстройств адаптации после пребывания в экстремальных условиях имеет высокую достоверность (p < 0,001).